2006
DOI: 10.1111/j.1744-697x.2006.00041.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecological importance of Neotyphodium spp. grass endophytes in agroecosystems

Abstract: Neotyphodium spp. fungal endophytes form symbiotic associations with agronomic grasses with expression ranging from mutualistic to parasitic. In general, endophyte infection frequencies seem more variable in natural compared to pastoral situations, suggesting that expression and benefits attributable to endophyte infection depend on the resource environment in which the host–endophyte complex was formed and the conditions under which it is being grown. Emerging evidence suggests that expression is not always m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(93 citation statements)
references
References 125 publications
5
85
1
Order By: Relevance
“…Therefore, E + grasses not only have adaptative advantages in stress environments, but can modify soil environments to ensure some competitive advantages. One explanation for better competitiveness of E + plants may be endophyte metabolites produced and released into the rhizosphere from fresh and dead plant material (Malinowski and Belesky 2006). Secondary metabolites of host-endophyte associations could be also involved in the fast weathering of micas in E + rhizospheres.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, E + grasses not only have adaptative advantages in stress environments, but can modify soil environments to ensure some competitive advantages. One explanation for better competitiveness of E + plants may be endophyte metabolites produced and released into the rhizosphere from fresh and dead plant material (Malinowski and Belesky 2006). Secondary metabolites of host-endophyte associations could be also involved in the fast weathering of micas in E + rhizospheres.…”
Section: Discussionmentioning
confidence: 99%
“…We also do not consider the complex case of the endophytic fungi inhabiting a series of fodder plants, which cause noxious effects to livestock because of their attitude to permeate host tissues with mycotoxins, and are also able to produce phytohormones [8][9][10]. A few excellent reviews on this bordering subject are available in the literature [11][12][13].…”
Section: Phytohormonesmentioning
confidence: 99%
“…Marks and Clay (1996) demonstrated an endophyte by temperature interaction, and Newman et al (2003) found an endophyte by N interaction on photosynthetic rates. Effects of endophyte infection on growth also strongly depend on host genotype, resource availability, and environmental stress (Belesky et al, 1989;Malinowski and Belesky, 2006;Morse et al, 2002;Cheplick and Cho, 2003;Hesse et al, 2003;Zabalgogeazcoa et al, 2006;Cheplick, 2007). In our study we saw significant cultivar by endophyte interactions on the regrowth of blades, which was only stimulated in 'AberDove' plants infected with the endophyte strain AR37, clearly demonstrating the importance of specific host plant-endophyte strain interactions and environmental conditions on overall physiological outcomes of the association.…”
Section: Effects Of Endophyte Infectionmentioning
confidence: 99%